Leader–member exchange (LMX) differentiation and work outcomes: conceptual clarification and critical review - Martin, R. (2018)
According to Leader-member Exchange (LMX) theory, leaders develop different quality relationships with followers in their team (termed LMX differentiation). An important theoretical question concerns how different LMX relationships within a team affect followers’ work outcomes. This paper provides a critical review of the concept of LMX differentiation. We propose that the LMX differentiation process leads to patterns of LMX relationships that can be captured by three properties (central tendency, variation, and relative position). We describe a taxonomy illustrating the different ways these properties have been conceptualized and measured. We identify two approaches to LMX differentiation as being a ‘perspective of the team’ (that are shared amongst team members) or a ‘perspective of the follower’ (subjective perceptions unique to each follower). These perspectives lead to different types of measures that predict different outcomes at the individual and team levels. We describe theoretical models employed to explain the effects of LMX differentiation (justice, social comparison, and social identity theories). Generally, the lower the within-team variation in LMX or the more a team member’s LMX is higher than the mean team LMX, the better are the work outcomes, but many moderators condition these effects. Finally, we identify some key areas for future research.